Acute intraabdominal hemorrhage from an aneurysm on uterine artery - Nakagawa, Tomoko; Kyukawa, Yutaka; Nakaoka, Yukiharu; Ninoi, Teruhisa; Nakamura, Kenji; Tsujita, Yujiro; Honda, Ken-ichi; Kurihara, Yasushi; Terada, Hiroyuki; Ando, Tetsuji; Yasui, Tomoyo; Sumi, Toshiyuki; et al. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 36-year-old woman was underwent emergency laparotomy for acute intraabdominal hemorrhage, but bleeding points were not found. Abdominal pains continued after the laparotomy, and rupture of aneurysm on uterine artery was found in angiography. An transcatheter arterial embolization was done for the uterine artery, and the aneurysm was found to disappear in 4-day-after the angiography. Rupture of an aneurysm on uterine artery should be considered for the causes of acute intraabdominal hemorrhage.